2018
DOI: 10.24879/201800120010085
|View full text |Cite
|
Sign up to set email alerts
|

Inteligência e desempenho escolar em crianças entre 6 e 11 anos

Abstract: O desempenho escolar faz parte do desenvolvimento de crianças e adolescentes, sendo um importante preditor de sucesso na vida adulta. O objetivodeste estudo foi investigar a relação entre inteligência e desempenho acadêmico, analisando a influência da idade, sexo e escola. Participaram 196 criançascom idade entre 6 a 11 anos, de escolas públicas e particulares da cidade de Vitória da Conquista, BA. Foram aplicados os Teste de Desempenho Escolare as Matrizes Progressivas Coloridas de Raven. As análises foram fe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0
2

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 26 publications
0
2
0
2
Order By: Relevance
“…Concerning the relation between intelligence and arithmetic performance, a strong correlation between the two variables was found, which suggests that students with higher scores in intelligence tend to present better performance in arithmetic. A study realized by Ribeiro and Freitas (2018) chose intelligence as a variable to explain 40 % of the variation in school performance. Another study developed by Mecca, Dias, Seabra, Jana and Macedo (2016) indicated that children with higher scores in reasoning tend to present better performance in arithmetic tasks.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Concerning the relation between intelligence and arithmetic performance, a strong correlation between the two variables was found, which suggests that students with higher scores in intelligence tend to present better performance in arithmetic. A study realized by Ribeiro and Freitas (2018) chose intelligence as a variable to explain 40 % of the variation in school performance. Another study developed by Mecca, Dias, Seabra, Jana and Macedo (2016) indicated that children with higher scores in reasoning tend to present better performance in arithmetic tasks.…”
Section: Discussionmentioning
confidence: 99%
“…Evidence shows that there is an effect of fluid intelligence in performance in mathematical skills (Colom, 2006;Ribeiro & Freitas, 2018), characterizing intelligence as an important predictor of educational performance (Roth et al, 2015). Fluid intelligence is linked to the capacity of individuals to realize tasks that involve reasoning, abstraction, planning, and the management of problems (Neubert, Mainert, Kretzschmar, & Greiff, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Evidências mostram que há efeito da inteligência fluida no desempenho em habilidades matemáticas (Colom, 2006;Ribeiro & Freitas, 2018), caracterizando a inteligência como um importante preditor do desempenho escolar (Roth et al, 2015). A inteligência fluida está relacionada à capacidade do indivíduo em realizar tarefas que envolvam raciocínio, abstração, planejamento e gerenciamento de problemas (Neubert, Mainert, Kretzschmar, & Greiff, 2015).…”
Section: Introductionunclassified
“…Em um outro estudo, não se apontam tais diferenças, uma vez que o trabalho teve como objetivo investigar a relação entre inteligência e desempenho acadêmico junto às crianças com idades entre 6 e 11 anos; analisando a idade, sexo e escola, não encontraram diferenças no gênero para o desempenho acadêmico (Ribeiro & Freitas, 2018). Esses dados são semelhantes à de uma outra pesquisa que avaliaram o desempenho escolar em crianças com baixo nível socioeconômico e queixa de desempenho escolar, e não encontraram diferenças de gênero tanto nos resultados do TDE (Teste de Desempenho Escolar), do Matrizes Progressivas de Raven, como na avaliação de inteligência geral (Marturano, Toller & Elias, 2005).…”
Section: Relação Entre Desempenho Acadêmico Gênero E Tipo De Escolaunclassified